Nontargeted identification of per- and polyfluoroalkyl substances in human follicular fluid and their blood-follicle transfer. (June 2020) - Kang, Qiyue; Gao, Fumei; Zhang, Xiaohua; Wang, Lei; Liu, Jiaying; Fu, Min; Zhang, Shiyi; Wan, Yi; Shen, Huan; Hu, Jianying
Highlights: HRMS-DIA method was developed for the nontargeted identification of PFAS. Fifiteen emerging PFAS were identified in follicular fluid. The blood-follicle transfers for emerging PFAS were reported for the first time. Abstract: The female reproductive toxicity of per- and polyfluoroalkyl substances (PFAS) has raised concerns, but knowledge about their human preconception exposure is limited. In this study, 15 emerging PFAS were identified in follicular fluid samples from healthy women by using high-resolution mass spectrometry, and Cl-substituted perfluoroalkyl ether sulfonates (Cl-PFESAs) including 4:2, 5:2, 6:2, and 8:2 Cl-PFESAs, 4:4 C8 perfluoroalkyl ether sulfonate (PFESA), C8 perfluoroalkyl ether carboxylate (PFECA), and C8 polyether PFECA (Po-PFECA) were detected in over 50% of 28 follicular fluid samples. Ten legacy PFAS were also detected, and the geometric mean concentration of PFOS was the highest (4.82 ng/mL), followed by PFOA (4.60 ng/mL), 6:2 Cl-PFESA (1.09 ng/mL), PFHxS (0.515 ng/mL), PFNA (0.498 ng/mL), and C8 PFECA (0.367 ng/mL). The blood-follicle transfer efficiencies for PFCAs decreased with increasing chain length (0.96 for PFHpA, 0.56 for PFTriDA), and the transfer efficiencies of C8 PFECA (0.78) was significantly higher than that of PFOA (0.76). The transfer efficiencies of 4:2 Cl-PFESA (0.73), 6:2 Cl-PFESA (0.75) and 8:2 Cl-PFESA (0.91) were significantly higher than that (0.70) of PFOS ( p  = 0.028, 0.026 and 0.002, respectively). This study constitutes the first report of the human oocyte exposure to emerging PFAS and their blood-follicle transfer abilities.